Social differences in postponing a General Practitioner visit in Flanders, Belgium: which low‐income patients are most at risk?. (13th March 2013) - Verlinde, Evelyn; Poppe, Annelien; DeSmet, Ann; Hermans, Koen; De, Jan; Van, Chantal; Willems, Sara
Abstract One of the main goals of primary care is providing equitable health‐care, meaning equal access, equal treatment and equal outcomes of healthcare for all in equal need. Some studies show that patients from lower socioeconomic groups visit a GP more often, while other studies show that they are more likely to postpone a visit to a GP. In this study, we want to explore within the social group of low‐income patients living in Flanders, Belgium, which patients have a higher risk of postponing a visit to a GP. A face‐to‐face questionnaire was administered among 606 low‐income users of Public Social Services. The questionnaire consisted of questions on socioeconomic and demographic characteristics, social networks, health and healthcare use. A multivariate logistic regression model was built to study the relationship between postponing or cancelling a GP visit which respondents thought they needed and variables on health, socio‐demographic background. The multivariate regression indicates that depression, self‐rated health and trust in the GP independently predict postponing a visit to a GP. Low‐income people with a low trust in the GP, people with a poor self‐rated health and people suffering from a severe depression are more likely to postpone or cancel a GP visit they thought they needed compared to other people on low incomes. This might indicate that the access to health‐care for low‐income people might be hindered by barriers which are not directly linked to the cost of the consultation.